Islamic communication system in Republic of Indonesia - Khurotin Anggraeni (Bahasa Indonesia, 2020)
The Indonesia is various cultures and language, Islam is a biggest religion in Indonesia, the communication form of Islam to understanding Islamic religion in various regions which has various culture and language. Islamic Communication system is a social action between Islamic organization with exchanging idea and raising the expectation of recognizing, understanding, acceptable to achieve specific goal (Da’wah) with multifaceted undertaking which require careful assessment of requirements, technology alternative, the allocation resources, economic impact and religion impact. The purpose of study is to describe and analysis Islamic communication system in Republic of Indonesia. The research method is done by library and information studies literature published was examined using content analysis method. The process included several steps: determining which journals and books met the inclusion criteria; selecting the research articles from the included journals and book; and extracting data from the relevant articles. As we know Indonesia has limit transportation and communication technology, very large area and has different language, culture and religion. The result of Islamic communication system is organization as problem solved on communication system. Islamic organization with multifaceted undertaking is required careful assessment on technology information, allocation resources, economic impact and religion impact. The role figure of leadership (usually namely Kyai) in communication is very important to connect with same organization. Interaction linkages between organizations will raise expectation on recognizing, understanding and acceptable.